A Competitive Trading Mechanism for Microgrid Group Considering Congestion Cost Allocation and Fair Distribution - Shanshan SHI; Ran FENG; Chen FANG; Shu LIU; Lirong DENG; Haojing WANG; Pu CHEN (Zhongguo dianli, 2024)
As the locational marginal pricing mechanism is hard to guarantee the real bidding of productive microgrids, the market efficiency may be decreased as a result. Considering the frequent occurence of transmission line conges-tion, this paper proposes a competitive trading mechanism for microgrid group considering congestion cost allo-cation and fair distribution. Based on the Vickrey-Clarke-Groves (VCG) theory, a payment model that promotes the real bidding of microgrids is proposed. Since the inherent problem of the VCG mechanism is the budget im-balance, and the existence of congestion in the system worsens this imbalance, this paper proposes a method to deal with the system budget imbalance based on the responsibility sharing method, in which the congestion cost is shared according to the impact of microgrid on the congestion, and the remaining system budget imbalance excluding the congestion cost is shared among consumption-oriented microgrids. The simulation results have ful-ly verified the effectiveness of the proposed mechanism.